1944
DOI: 10.1128/jb.47.1.15-25.1944
|View full text |Cite
|
Sign up to set email alerts
|

The Antibacterial Action of Surface Active Cations

Abstract: The antibacterial action of surface-active cations was reported by Hartmann and Kiigi (1928) on the basis of observations made by Doerr. Domagk (1935) gave a detailed description of the bacteriological properties of a very potent member of this group. Notwithstanding the considerable attention which these discoveries aroused, as shown by the number of investigations reported in the literature, apparently no attempt has been made to relate the antibacterial action of surface-active cations to that of other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

1945
1945
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…Just as in the case of the benzotriazolium derivatives (Valko and DuBois, 1944) with which, in agreement with Rawlins et al (1943), we could not reproduce Westphal's (1940a, 1940b) results,' here again we found that the di-n-octyl derivatives were not superior to the hexadecyl or dodecyl homologs, as Kuhn, Jerchel, and Westphal (1940) claim.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Just as in the case of the benzotriazolium derivatives (Valko and DuBois, 1944) with which, in agreement with Rawlins et al (1943), we could not reproduce Westphal's (1940a, 1940b) results,' here again we found that the di-n-octyl derivatives were not superior to the hexadecyl or dodecyl homologs, as Kuhn, Jerchel, and Westphal (1940) claim.…”
Section: Discussionsupporting
confidence: 84%
“…It is obvious that the determination of the average chemical composition is of no value in the control of these materials, and fractionation methods have to be used for their chemical control. At the same time, the results indicate that the determining factor in the antibacterial activity is not the average composition of a mixed micelle but the independent contribution of each single component, except in the special cases where competitive effects (Valko and DuBois, 1944) come into play. Our results, as presented in tables 3 to 10, clearly demonstrate that maximum antibacterial potency is not reached with the same chain length of the high molecular aliphatic chain in various homologous series.…”
Section: Discussionmentioning
confidence: 91%
“…Frequent references are found in the literature emphasizing the synergistic or antagonistic effect of a particular substance upon the biological activity of other, chemically unrelated compounds. In the case of the germicides, it has been shown by Domagk (1935), Baker, Harrison, and Miller (1941), Valko and DuBois (1944), and many others that cationic and anionic detergents will neutralize each other. Such reversal of the activity of quaternary ammonium compounds have been demonstrated with soaps, sodium taurochoate, sodium lauryl sulfate, suramin sodium and many other anionic agents.…”
Section: Discussionmentioning
confidence: 99%
“…I C6H5CH2-N-R C1-L AH3 J I activity of the mixture (1)(2)(3). The current methods of identification of benzalkonium chloride solutions according to the USP (4), rely upon titrimetric analysis of total alkyl benzyldimethylammonium chloride based upon potassium iodate equivalents.…”
Section: 'mentioning
confidence: 99%